Recruitment patterns of freshwater amphidromous fishes (Pisces: Gobiidae, Eleotridae) to the Cimaja estuary, Palabuhanratu Bay - Charles P.H Simanjuntak; Faqih Baihaqi; Tri Prabowo; Shafira Bilqis A; Sulistiono Sulistiono; Ayu Ervinia (Jurnal Iktiologi Indonesia, 2021)
The sustainability of amphidromous fishes is determined by the success of the larval recruitment process from marine to freshwaters habitats. This study aimed to determine the recruitment pattern of freshwater amphidromous fish to the Cimaja River estuary, Palabuhanratu Bay in terms of season and daily. Amphidromous fish were caught monthly on the 25th of Hijri or waning crescent from December 2020 to August 2021. Sampling in one whole day with observation intervals every 4 hours was carried out in June 2021 to reveal the time of larvae and juveniles of the amphidromous fish recruit to the Cimaja River estuary. A total of 13 species of amphidromous fishes representing five genera and two families was captured. The recruitment of amphidromous fishes into the Cimaja River occurs between the peak of the rainy season to dry season. Generally, amphidromous recruit into the estuary waters of the Cimaja River is at the juvenile stage (11.9-21.8 mm body length). However, the recruitment of some amphidromous fish species appears at the postflexion stage (6.9-11.9 mm BL). Based on diel observations, larvae and juveniles of amphidromous fish are generally preferred to recruit to the Cimaja River estuary in the early morning (03:00 am) and afternoon (03:00 pm). Recruitment of amphidromous fish larvae to the Cimaja River follows a semi-diurnal tidal cycle which is a tidal type in Palabuhanratu Bay. Amphidromous fishes use tidal flux to recruit and migrate upstream of the Cimaja River through estuaries. Abstrak Keberlanjutan sumber daya ikan amfidromus ditentukan oleh keberhasilan proses rekrutmen larva dari habitat laut menuju perairan tawar. Penelitian ini bertujuan untuk mengetahui pola rekrutmen ikan amfidromus air tawar menuju perairan estuari Sungai Cimaja, Teluk Palabuhanratu ditinjau dari musim dan harian. Ikan amfidromus ditangkap setiap bulan pada tanggal 25 Hijriah atau awal bulan baru dari Desember 2020 sampai Agustus 2021. Sampling dalam satu hari penuh dengan interval pengamatan setiap 4 jam dilakukan pada Juni 2021 untuk menentukan waktu larva dan yuwana ikan amfidromus rekrut ke estuari Sungai Cimaja. Sebanyak 13 spesies anak ikan amfidromus mewakili lima genera dan dua famili ditemukan. Puncak rekrutmen anak ikan amfidromus di Sungai Cimaja terjadi antara pertengahan musim penghujan sampai musim kemarau. Anak ikan amfidromus yang melakukan rekrutmen ke perairan estuari Sungai Cimaja umumnya berada pada stadia yuwana (panjang tubuh 11.9-21.8 mm). Namun proses rekrutmen ke wilayah estuari Cimaja pada beberapa spesies ikan amfidromus lainnya terjadi pada stadia postflexion (6,9-11,9 mm). Berdasarkan pengamatan harian ditemukan bahwa larva dan yuwana ikan amfidromus umumnya memilih rekrut ke estuari Sungai Cimaja pada dini hari (pukul 03:00) dan sore hari (15:00). Puncak rekrutmen larva ikan amphiromus menuju Sungai Cimaja mengikuti siklus pasang semi-diurnal yang merupakan tipe pasang di Teluk Palabuhanratu. Ikan amphidromous memanfaatkan gelombang pasang untuk rekrut dan beruaya ke arah hulu Sungai Cimaja melewati daerah estuari.